PRINSIP PENYELENGGARAAN PEMBELAJARAN ORANG DEWASA PADA LOKAKARYA KOMUNITAS BELAJAR I PROGRAM SEKOLAH PENGGERAK ANGKATAN II PROPINSI BENGKULU UNTUK MEWUJUDKAN EKOSISTEM SEKOLAH YANG BERDIFERENSIASI - Putra, Ari; Stiadi, Elwan; Dwi Palenti, Citra; Gusti, Ririn; Sofino, Sofino; Saputra, Adif Jawadi (LPPM Universitas Ibn Khaldun, Bogor, 2024)
This study aims to explore how the andragogy approach can be used in workshops of the Sekolah Penggerak Program to realize student-centered learning and school ecosystems. This approach involves principals, school supervisors, and teachers as participants in the workshop, with a focus on participant involvement as the key to the success of adult learning. The study uses a qualitative approach with data collection through interviews, observations, and documentation. The principles of andragogy are the main foundation in organizing the Community Learning Workshop, where participants are actively involved in the learning process. This workshop becomes an effective model because it allows adults to learn from collective experiences and knowledge within the community. In the context of adult education, community learning workshops become a relevant strategy to achieve the goals of Adult Education programs. The learning approach in these workshops follows the MERDEKA flow, which includes stages starting from self, exploration of concepts, collaboration space, guided reflection, contextual demonstration, elaboration of understanding, connection between materials, and (action) plan, totaling 8 hours of lessons. Organizing adult learning through community learning workshops is one of the relevant strategies to achieve the goals of the Sekolah Penggerak Program in improving access and quality of education for the community, including adult education. Therefore, it is important to understand the principles underlying the organization of adult learning in community learning workshops in the Sekolah Penggerak Program